Literature Review of Post-Traumatic Stress Disorder Interventions Among Prisoners - Nur Oktavia Hidayati; Iis Kania Nurasiah Jamil; Marlynda Maya Triana; Lisdiawati Lisdiawati; Vina Nurdiansari (Jurnal Keperawatan Jiwa, 2023)
Anyone, including prisoners, can experience traumatic events. Prison life with its many disputes, pressures and constraining restrictions, as well as the loss of freedom can cause prisoners to experience chronic stress. Prison related stressors can worsen PTSD symptoms in prisoners. Nurse can give appropriate interventions for prisoners suffering from PTSD as part of the endeavor to overcome this. The aim of this research study was to identify different PTSD therapies for convicts. A literature review was employed as the technique. Articles searched in databases and search engines PubMed, EBSCO, and Google Scholar with keywords in English: intervention, PTSD, prisoners, and keywords in Indonesian: intervention, PTSD, and prisoner, publication year 2015 - 2021, full text and open access. Mindfulness-based Relapse Prevention (MBRP), Eye Movement Desensitization and Reprocessing (EMDR), Evidence-Based Psychotherapy (EBPs), Interpersonal Psychotherapy (IPT), and Group Interpersonal Psychotherapy (IPT) were five papers discovered regarding therapies for inmates with PTSD. The study indicated that all therapies included in the analysis of the literature were effective in reducing PTSD symptoms in inmates.